Photothermal imaging using non-contact photopyroelectric method - Amran, Azura; Saat, Nor Kamilah; Tamchek, Nizam; Ting, Lee Mon (Universiti Kebangsaan Malaysia, 2020)
Photothermal imaging is a non-destructive and contactless technique for testing and monitoring defect of materials. This work is demonstrated thermal images for film sample of Al, Cu, Ni, and Cu with artificial defect with sampling area of 10 mm × 12 mm (21 × 25 pixels), 10 mm × 14 mm (21 × 29 pixels), 10 mm × 14 mm (21 × 29 pixels), 10 mm × 10 mm (21 × 21 pixels) respectively, acquired by raster scanning with the step size of 500 µm at fixed frequency modulation of 6 Hz and lock in detection in the range of 50 to 500 mV depending of studied material. The thermal image of defect sample is successfully acquired by introducing artificial defect onto the sample of Cu film. The thermal signal is obtained by taking transmission measurement which is defined by the ratio of intensity with sample to without sample. This paper also involves a photopyroelectric non-contact configuration for thermal diffusivity of the Al, Cu, and Ni film samples. Normalization procedure was used to wipe out the amount of photopyroelectric cell media parameter that should usually known before the sample’s thermal diffusivity could be decided. In this case, sample Al, Cu, and Ni were nearly to literature values but therefore justified the suggested model, the thermal diffusivity acquired.